Postsynaptic α-Neurotoxin Gene of the Spitting Cobra, Naja naja sputatrix: Structure, Organization, and Phylogenetic Analysis - Afifiyan, Fatemeh; Armugam, Arunmoziarasi; Tan, Chee Hong; Gopalakrishnakone, Ponnampalam; Jeyaseelan, Kandiah

(untitled) (Genome Research, 1999)
The venom of the spitting cobra, Naja naja sputatrixcontains highly potent α-neurotoxins (NTXs) in addition to phospholipase A2 (PLA2) and cardiotoxin (CTX). In this study, we report the complete characterization of three genes that are responsible for the synthesis of three isoforms of α-NTX in the venom of a single spitting cobra. DNA amplification by long-distance polymerase chain reaction (LD-PCR) and genome walking have provided information on the gene structure including their promoter and 5′ and 3′ UTRs. Each NTX isoform is ∼4 kb in size and contains three exons and two introns. The sequence homology among these isoforms was found to be 99%. Two possible transcription sites were identified by primer extension analysis and they corresponded to the adenine (A) nucleotide at positions +1 and −45. The promoter also contains two TATA boxes and a CCAAT box. Putative binding sites for transcriptional factors AP-2 and GATA are also present. The high percentage of similarity observed among the NTX gene isoforms of N. n. sputatrix as well as with the α-NTX and κ-NTX genes from other land snakes suggests that the NTX gene has probably evolved from a common ancestral gene.[The genomic DNA sequences reported in this paper have been submitted to GenBank databases under accession nos. AF096999 to AF097001.]